MANAGEMENT OF SEKETAK RIVER, CENTRAL JAVA, INDONESIA BASED ON DETERMINATION OF WATER QUALITY STATUS AND POLLUTION LOAD APPROACH - A’in, Churun; Rudiyanti, Siti; Suryanti, Suryanti; Zevriawan, Aldhimas Bagus (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2024)
Due to the presence of renowned universities, Tembalang, Semarang City, is experiencing rapid development. However, this development not only brings positive impacts but also raises environmental issues, one of which is river pollution. Seketak River, a ±10.5 km long river that has its headwaters in Banyumanik Subdistrict and empties into Diponegoro University's Education Reservoir, is one of the affected areas. This river pollution has the potential to disrupt water quality and aquatic biota life. The source of pollution is suspected to come from domestic, industrial, and livestock waste around the Seketak watershed. Therefore, intensive research was conducted to analyze the status of water quality and pollution load based on point sources. This research aims to provide recommendations for proper management and control of pollution. Data were collected during the transitional season (dry to rainy) using the Pollution Index (IP) method based on the Decree of the Minister of Environment No. 115 of 2003 and the Pollution Load (BP) method. The research involved four sampling points, each representing a pollutant source (industry, settlement, campus, and livestock), with two repetitions. The results showed that the average IP value of Seketak River was in the lightly polluted category, referring to the Class II Quality Standard of PP No. 22 of 2021. In the first repetition, the IP value was 2.87, while in the second repetition it reached 3.26. The Pollution Load Analysis identified 5 variables that exceeded the maximum load including Nitrite, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), iron (Fe) and lead (Pb). These findings emphasize the importance of integrated management efforts to mitigate pollution in Seketak River.